Truths I never told you - Rimmer, Kelly (Graydon House, 2020)
"With her father recently moved to a care facility, Beth Walsh volunteers to clear out the family home and is surprised to discover the door to her childhood playroom padlocked. She's even more shocked at what's behind it--a hoarder's mess of her father's paintings, mounds of discarded papers and miscellaneous junk in the otherwise fastidiously tidy house. As she picks through the clutter, she finds a loose journal entry in what appears to be her late mother's handwriting. Beth and her siblings grew up believing their mother died in a car accident when they were little more than toddlers, but this note suggests something much darker. Beth soon pieces together a disturbing portrait of a woman suffering from postpartum depression and a husband who bears little resemblance to the loving father Beth and her siblings know. With a newborn of her own and struggling with motherhood, Beth finds there may be more tying her and her mother together than she ever suspected." -- Amazon.